Corpus-based critical discourse analysis of reporting practices in English news reports on public health event in China and United States - Li, Zhuoran; Zhao, Ronghui; Lou, Baocui (Frontiers in Psychology, 2023)
Introduction Reporting speech is a basic form of human language, and reporting practices play a key role in news report. As one of the important rhetorical devices to introduce the reported speech, reporting verbs can help the readers understand the source of the reported speech and the attitude of the journalist or the media toward the reported information. Method This study examines the features of reporting practice in Chinese and American news reports on public health emergency by investigating the use of reporting verbs from the perspectives of critical discourse analysis. Two English news corpora of COVID-19 pandemic are built, namely, the China Daily News Corpus and the New York Times News Corpus, with 50 news texts in each corpus. The corpus analysis tool AntConc 3.3.5 is used to conduct concordance analysis. Results and discussion It is found that Chinese and American news reports tend to use roughly the same high-frequency reporting verbs in reporting the COVID-19 pandemic. Chinese and American news corpora show difference in the distribution feature of high-frequency reporting verbs in terms of semantic category. Both Chinese and American news reports use speech reporting verbs most frequently, indicating an objective attitude toward the reported event, and use speech reporting verbs and speech act reporting verbs to introduce the reported speech with comparatively higher degree of certainty. American news reports frequently use mental reporting verbs to show the attitude of uncertainty toward the reported speech, and Chinese news reports probably need to raise the awareness of using mental reporting verbs to express the opinions and attitude of the common people or the authority. The findings of this study can provide insights into the research on reporting strategies of news reports on emergencies in China for foreign audience.